Gender Differences in Entry Wages and Early Career Wages - Astrid Kunze (Institute for the Study of Labor (IZA), 2002)
In this paper we investigate the evolution of the gender wage gap over early careers of skilled workers in Germany using administrative longitudinal data. Advantages of the data for this type of analysis are that we observe complete work and skill accumulation histories from the beginning for up to 13 years in the labour market. Descriptives show an entry wage differential of 22 percent between male and female full-time workers. The differential stays almost constant throughout the first 8 eight years in the labour market. Adopting a human capital model, we investigate the sources for the differential by the separate analysis of entry wages and early career wages.
Keywords: J7; J3; J16; 330; male-female wage differentials; human capital; entry wages; work experience; Lohndifferenzierung; Berufseinstieg; Geschlecht; Frauenarbeitslohn; Erwerbsverlauf; Schätzung; Deutschland; Berufserfahrung